The Dependence of the Rupture Probability on the Mass Number of the Fissionable Nucleus - Auliya, Z.; Kurniadi, R.; Irwanto, D. (National Research and Innovation Agency, 2025)
The relationship between the mass number of fissionable nuclei and fission yield is generally known through the fission barrier. The deformation energy of the SEMF determines the probability of the formation of fission products. The use of deformation energy is very impractical because it goes through many calculation stages. For this reason, the Neck Rupture Model was introduced, namely a model that shortens the stages of the calculation process through the rupture probability formula. In this paper, a new technique was introduced that adds the dependence of the rupture probability on the mass number of the nucleus that will undergo fission. Apart from this, this technique also obtained better fission yield calculation data compared to the previous technique. The fission yield calculations of Uranium isotopes at an energy of 14 MeV will be shown.